2013
DOI: 10.1051/parasite/2013036
|View full text |Cite
|
Sign up to set email alerts
|

Neospora caninumantibodies in dairy cows and domestic dogs from Vojvodina, Serbia

Abstract: Neospora caninum, the causative agent of neosporosis, is a protozoan parasite responsible for high rate of abortion in cattle worldwide. In dogs, consequences of infection vary from severe neuromuscular disorders to asymptomatic infection and shedding of environmentally resistant oocysts. In this study, we determined the occurrence of N. caninum antibodies in dairy cattle and dogs in Vojvodina (Northern Province of Serbia) and possible risk factors. N. caninum antibodies were found in 15.4% (55/356, CI 95%:12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 11 publications
1
4
3
1
Order By: Relevance
“…The higher prevalences documented in older dogs suggest most of them become infected after birth. In the present study, as well as in some others [10, 11, 13], no significant differences were observed between young and old animals. Nevertheless, it is important to point out that the number of dogs in the young group (i.e., 2–11 months old) was smaller than the adult group.…”
Section: Resultssupporting
confidence: 66%
“…The higher prevalences documented in older dogs suggest most of them become infected after birth. In the present study, as well as in some others [10, 11, 13], no significant differences were observed between young and old animals. Nevertheless, it is important to point out that the number of dogs in the young group (i.e., 2–11 months old) was smaller than the adult group.…”
Section: Resultssupporting
confidence: 66%
“…We didn’t test the second batch samples because of non availability of reagents for testing of N. caninum by NAT, or IFA, or cELISA in China. Compared with other countries [10-13], the prevalence of N. caninum antibody was low in East Asia [14,15]; also it is low in this study. Although a comparison of different serological tests (NAT, IFA, cELISA) for the detection of N. caninum antibodies in dogs has not been made, it is generally accepted that results by NAT and IFA are comparable because both tests assess antibodies directed against whole tachyzoites [1].…”
Section: Resultscontrasting
confidence: 55%
“…Only asexual life stages of N. caninum have been observed in intermediate hosts (tachyzoites and encysted bradyzoites), including cattle [5, 31]. Previous studies have shown that the prevalence of N. caninum in dogs ranges anywhere from 2.1 to 36.4% in Europe, and 0.54 to 34.91% in central China [2, 10, 11, 17, 22, 2830].…”
Section: Introductionmentioning
confidence: 99%